2020
DOI: 10.2334/josnusd.18-0282
|View full text |Cite
|
Sign up to set email alerts
|

Association of low fetuin-A levels with periodontitis in community-dwelling adults

Abstract: Fetuin-A is a liver-secreted glycoprotein isolated from fetal bovine serum. Recent reports of its several pathological functions suggest an association between fetuin-A and systemic diseases. This study therefore examined the correlation between serum fetuin-A level and periodontal status. Data from 356 middle-aged and elderly adults who underwent health examinations in Goto, Japan, during the period from 2008 through 2010 were analyzed. Systemic and periodontal measurements were recorded, and serum fetuin-A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…Likewise, a study published by Furugen et al., 18 displayed a significant down regulation of serum fetuin‐A levels with hastened periodontal destruction. Hence, considerable evidence deputes serum fetuin‐A to authentically reflect the extent of periodontal tissue destruction and predict disease progression.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Likewise, a study published by Furugen et al., 18 displayed a significant down regulation of serum fetuin‐A levels with hastened periodontal destruction. Hence, considerable evidence deputes serum fetuin‐A to authentically reflect the extent of periodontal tissue destruction and predict disease progression.…”
Section: Discussionmentioning
confidence: 84%
“…Upregulated serum fetuin‐A levels after NSPT, as noted in the present study, could help curb systemic calcification that is otherwise known to promote multiple systemic complications. Hence, fetuin‐A could act as a potential conduit, linking a site‐specific inflammatory condition like periodontitis to systemic disorders 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetuin-A'nın inflamasyon sırasında salgılanan TNF, IL-1, IL-6, interferon gama gibi önemli sitokinler ile negatif korelasyon gösterdiği belirtilmiştir [3]. Fetuin-A'nın anti-inflamatuvar özellikleri göz önüne alındığında periodontal hastalıkla ilişkili olabileceği de düşünülmektedir [12][13][14]. Periodontal hastalıklı bireylerde salya [15], serum [12,14] ve diş eti oluğu sıvısı (DOS) (14) Fetuin-A'nın azaldığı ve periodontal tedavi sonrasında arttığı rapor edilmiştir [13].…”
Section: Introductionunclassified
“…Periodontitis is one of the most common oral diseases worldwide. Studies have shown that the invaded pathogens could adhere to the gums and periodontal tissues, multiply, grow, and the metabolic substance produced by the invaded pathogens can activate the immune system, causing edema and bleeding of soft tissue, and formation of periodontal pockets [1,2]. The biggest hidden danger of periodontitis is that periodontitis can induce other systems disease.…”
Section: Introductionmentioning
confidence: 99%